Spectrophotometric Determination of Paracetamol and Orphenadrine Citrate in Tablet - Nejem, Leon; Antakli, Saad; Bagdashe, Helen (Asian Journal of Chemistry, 2012)
A simple and rapid spectrophotomitric method has been developed to determine orphenadrine citrate and paracetamol in tablet formulations. The first step was based on the reaction of orphenadrine citrate with 1-amino naphthalene and sodium nitrite with heating for 6 min at 50 ºC to give an orange colour having a maximum absorbance at 462 nm. The optimization of the reaction conditions is investigated. In the second step, paracetamol was analyzed after solving it in distilled water by taking the first order derivative spectroscopy and that to eliminate spectral interference with orphenadrine citrate. Beers law is obeyed in the concentration ranges 4.61-80.76 μg/mL and 0.75-30 μg/mL for orphenadrine citrate and paracetamol, respectively. The molar absorptivity, limit of detection, limit of quantification, Sandell sensitivity and linearity are also calculated. The average per cent recovery was found to be 99.90 ± 0.14 % for paracetamol and 99.80 ± 0.05 % for orphenadrine citrate.